Effect of delayed reinforcement on skill acquisition during discrete‐trial instruction: Implications for treatmen‐integrity errors in academic settings. Issue 1 (17th November 2015) - Carroll, Regina A.; Kodak, Tiffany; Adolf, Kari J.
Abstract : We used an adapted alternating treatments design to compare skill acquisition during discrete‐trial instruction using immediate reinforcement, delayed reinforcement with immediate praise, and delayed reinforcement for 2 children with autism spectrum disorder. Participants acquired the skills taught with immediate reinforcement; however, delayed reinforcement decreased the efficiency and effectiveness of discrete‐trial instruction. We discuss the importance of evaluating the influence of treatment‐integrity errors on skill acquisition during discrete‐trial instruction.